Entrepreneurship in Islam (Principles and Strategies for the Success of the Prophet Muhammad SAW in Trading) - Zian Salsabila Bidaula; Sitti Maulida; Holilur Rahman (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2024)
In the Islamic view, entrepreneurship does not only have material capabilities, but a Muslim entrepreneur will use his religion as a guide in his activities, including managing his business to avoid the goal of justifying all means. Therefore, it is necessary to know the principles and strategies of the Prophet Muhammad SAW in trading, where there are several principles that we can emulate from the Prophet Muhammad saw, namely Siddiq, Amanah, Fathanah and Tabligh. This article uses the Pustaka study research method (library research) which is a method of collecting data by understanding and studying theories from various literature related to research, where this research can be obtained from several sources such as books, manuscripts, jurna or from reports on previous research results. In this article we discuss the principles and strategies for the success of the Prophet Muhammad SAW in trading, which in this article discusses the biography of the Prophet Muhammad SAW, the principles and strategies for the success of the Prophet Muhammad SAW in trading.